1998
DOI: 10.1680/geot.1998.48.3.301
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to optimum design of piled rafts

Abstract: The majority of piled raft foundations have been designed ignoring any contribution from the raft or pile cap, although it is well known that the raft plays an important role in the overall performance. In such conventional designs, the overall settlement of the foundation is likely to be very small, owing to the installation of more piles than are necessary. However, from an economical point of view, it is preferable that the foundation is designed in such a way that the average and differential settlements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(52 citation statements)
references
References 7 publications
5
47
0
Order By: Relevance
“…Plan dimension of raft is considered as 10 m × 10 m which is discretized into 0.5 m × 0.5 m small elements based on a convergence study. A moderately rigid raft is selected in this study considering the relative stiffness of raft and soil (k rs ) as suggested by Horikoshi and Randolph (1998)…”
Section: 1mentioning
confidence: 99%
“…Plan dimension of raft is considered as 10 m × 10 m which is discretized into 0.5 m × 0.5 m small elements based on a convergence study. A moderately rigid raft is selected in this study considering the relative stiffness of raft and soil (k rs ) as suggested by Horikoshi and Randolph (1998)…”
Section: 1mentioning
confidence: 99%
“…The IFM is strictly not applicable to situations where the pile cap is in contact with the ground. However, given that the majority of piled rafts are designed ignoring any contribution from raft-soil interaction (Horikoshi and Randolph 1998), the analyses presented herein will be of interest to geotechnical designers. Moreover, a reliance on the contribution of the raft-soil resistance can lead to unconservative design in situations where the occurrence of ground surface settlement and/or scour by water current, for example, is possible.…”
Section: Applicability To Piled Raftsmentioning
confidence: 99%
“…In this section, the FE model of a circular raft is validated using centrifuge test data reported by Horikoshi and Randolph [37]. The purpose of this validation is to build confidence in the relevance and accuracy of the FEA for piled raft foundations.…”
Section: Validation and Verificationmentioning
confidence: 99%